The territorial anguish and the burrow of the Modern - Cesarone, Virgilio (Itinerari, 2024)
Starting from the habit of a tribe in Australia, the contribution illustrates the characteristics of the organisation of space, public and private, in use in populations characterised by a religious vision. Juxtaposed to this attitude of living, the description of the burrow in Kafka’s short story is taken as a modern paradigm. To the openness between the various levels of the spatial realms of religious man, modern man contrasts his enclosure in a securitarian isolation. And yet the passivity of such a subject could provide a liberating way out.